ELECTROMYOGRAPHY AND ITS IMPORTANCE FOR DENTAL PRACTICE - Hurjui Loredana Liliana; Hurjui Ion; Cristina Claudia Tărniceriu; Saveanu Iulia; Balcoș Carina; Armencia Oana Adina; Mitrea Mihaela; Grădinaru Irina (Romanian Dental Association for Education, 2020)
Electromyography (EMG) as a method of investigation and analysis has entered in the functional exploration of the orofacial muscles in clinical practice and functional dental exploration first being related to the diagnosis of malocclusions. Currently is frequently present in oro-dento-maxillo-facial practice and used for cases requiring diagnostic clarification in the neuromuscular pathology associated to the stomatognathic system and also as a tool for functional assessment of fineness useful in reconstructive surgery (especially post-traumatic) and oro-maxillo-facial neurology (electro-neuromyography), orthodontics, prosthetics, facial aesthetics and complex oral rehabilitation, in order to correct morphological and/or myofunctional imbalances in the stomatognathic territory and the neck region. Another important aspect of the usefulness of EMG is the involvement of this investigation method in fundamental research such as physiology, pathophysiology and electrophysiology regarding muscles and nerves (motor units), resting, action and evoked potentials of various muscular, individual or fascicular complex structures and their ability to adapt, compensate and functionally supplement in different circumstances.